2021
DOI: 10.3389/fcell.2021.654715
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone 1 Receptor Signaling in Dental Mesenchymal Stem Cells: Basic and Clinical Implications

Abstract: Parathyroid hormone (PTH) and parathyroid hormone-related protein (PTHrP) are two peptides that regulate mineral ion homeostasis, skeletal development, and bone turnover by activating parathyroid hormone 1 receptor (PTH1R). PTH1R signaling is of profound clinical interest for its potential to stimulate bone formation and regeneration. Recent pre-clinical animal studies and clinical trials have investigated the effects of PTH and PTHrP analogs in the orofacial region. Dental mesenchymal stem cells (MSCs) are ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 244 publications
(306 reference statements)
0
8
0
1
Order By: Relevance
“…Interestingly, moreover, subpopulations of murine dental follicle cells were discovered in murine tooth germs. Ono and colleagues showed that murine dental follicles contain different subpopulations that can be distinguished by expressing specific genes such as the osteogenic transcription factor Osterix, PTHrP, and Gli1, which are involved in the Hedgehog signaling pathway, which contributes to both tooth eruption and periodontal development [ 4 , 8 , 30 ]. However, how these murine DFC populations relate to isolated human DFCs is unknown and is a worthwhile research topic for the future.…”
Section: Isolation Of Cells From Human Dental Folliclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, moreover, subpopulations of murine dental follicle cells were discovered in murine tooth germs. Ono and colleagues showed that murine dental follicles contain different subpopulations that can be distinguished by expressing specific genes such as the osteogenic transcription factor Osterix, PTHrP, and Gli1, which are involved in the Hedgehog signaling pathway, which contributes to both tooth eruption and periodontal development [ 4 , 8 , 30 ]. However, how these murine DFC populations relate to isolated human DFCs is unknown and is a worthwhile research topic for the future.…”
Section: Isolation Of Cells From Human Dental Folliclesmentioning
confidence: 99%
“…During the early stages of tooth development, the dental follicle, sometimes called the “dental sac“, forms a sac-like tissue around the other two tooth germ tissues ( Figure 1 ). The dental follicle takes part in the morphology of the tooth crown and it is also involved in the developmental processes of tooth root formation [ 7 , 8 ]. Cells from the dental follicle (DFCs) are therefore also precursors of all mineralizing and non-mineralizing cells of the periodontium.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, protective healing bioactivities occur simultaneously with the pathological process in AP, which is mainly led by mesenchymal stem cells (MSCs), which are primitive cells characterized by self-renewal and a multilineage differentiation potential. Physiological MSC clusters derived from the dental region include orofacial bone-marrow-derived mesenchymal stem cells (OMSCs), periodontal ligament stem cells (PDLSCs), dental pulp stem cells (DPSCs), stem cells from human exfoliated deciduous teeth (SHEDs), gingival mesenchymal stem cells (GMSCs), the stem cells from the apical papilla (SCAPs), and dental follicle progenitor cells (DFPCs) [ 5 , 6 ]. Among them, OMSCs and SCAPs have been demonstrated as critical participants in the repair process in AP [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, OMSCs and SCAPs have been demonstrated as critical participants in the repair process in AP [ 7 , 8 , 9 , 10 , 11 , 12 ]. Research applying dental MSCs in vivo has shown their potential in the formation of bony tissues and a root–periodontal-like complex as well as pulp regeneration [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ebenso legt eine Studie von Pieles et al nah, dass eine hohe endogene Expression von PTHrP einen positiven Einfluss auf die osteogene Differenzierung von humanen dentalen Follikel Stammzellen aufweist 34 . Eine umfassende Darstellung der Rolle des PTH1R Signalwegs in dentalen mesenchymalen Stammzellen ist auch dem kürzlich erschienenem Review von Lyu et al 35 zu entnehmen.…”
Section: Introductionunclassified